Viral Metagenomics Analysis of Rodents From Two Border Provinces Located in Northeast and Southwest China - Zhao, Teng; Dang, Yun-qi; Wang, Ao-nan; Gao, He-ting; Zhang, Heng-duan; Xing, Dan; Li, Bo-qi; Li, Yong-jiu; Liu, Zhu; Li, Chun-xiao (Frontiers in Microbiology, 2022)
Objective: Wild animal pathogen surveillance will help to understand the next possible pandemic in advance. Rodent, which had close contact with human beings, was generally regarded as e a key factor for zoonosis diseases control. Curiosity with the rodent virus composition variation in diverse ecology, we conducted a study on the viral infection of diverse species rodents inHeilongjiang and Yunnan Provinces, located in northeastern and southwestern China. Methods: Viral metagenomic sequencing and bioinformatic analysis were performed to obtain the different distribution of rodent-borne viruses in Heilongjiang and Yunnan Provinces, China. After viral culture and PCR confirmation, genome and phylogenetic quantitative analysis was performed on the detected hantavirus (HV) and Beilong virus (BeiV). Results: 19 in three species and 35 in five species of rodents were collected from Heilongjiang and Yunnan Provinces, respectively. Through the number and species of rodents trapped in Northeast was less than the ones in Southwest, virus annotated from rodents in Heilongjiang were more diversity than that in Yunnan. Rodents carried 22 virus families in Heilongjiang and 13 families in Yunnan. Sequences assembled from Rattus norvegicus were annotated to M, L and S segments of HV, all were clustered within the SEOV type. There were 2 (R81Q, S698T) and 4 (K153R, M168I, I279S, R1790K) amino acid site substitutions in M and L comparing with the most homologous strains. Two Beiv isolated from Rattus norvegicus were closely related to Beiv from brown rats in HongKong with high bootstrap of >90% in N segment and >95% in L segment. They were further clustered with Tailam virus, forming a distinct group in Paramyxoviridae. Conclusion: The rodents from Heilongjiang and Yunnan located in northeast and southwest China had different viral spectrum, only one third (10/32) virus families were detected in both area. The predominant viruses were HV and BeiV in Hantaviridae and Paramyxoviridae families, respectively. Rodent-borne viruses in same species were similar in different long distance area, owing to their similar close contact with human habitats and human activities. More attention should be paid to the monitoring of neglected rodent-borne viruses, especially the opportunistic virus with low load temporarily.